2013
DOI: 10.1371/journal.pone.0069543
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Transcriptome of Coptotermes formosanus Shiraki Workers: The Defense Mechanism

Abstract: Formosan subterranean termites, Coptotermes formosanus Shiraki, live socially in microbial-rich habitats. To understand the molecular mechanism by which termites combat pathogenic microbes, a full-length normalized cDNA library and four Suppression Subtractive Hybridization (SSH) libraries were constructed from termite workers infected with entomopathogenic fungi (Metarhizium anisopliae and Beauveria bassiana), Gram-positive Bacillus thuringiensis and Gram-negative Escherichia coli, and the libraries were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 87 publications
1
38
0
Order By: Relevance
“…Furthermore, no distinct regulation patterns could be detected, with only few genes being differentially expressed (>2 fold) between symbiotic and aposymbiotic individuals. These observations are in line with other studies, demonstrating the constitutive expression of immune signaling pathway genes [34] .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, no distinct regulation patterns could be detected, with only few genes being differentially expressed (>2 fold) between symbiotic and aposymbiotic individuals. These observations are in line with other studies, demonstrating the constitutive expression of immune signaling pathway genes [34] .…”
Section: Discussionsupporting
confidence: 93%
“…The immune response is another aspect of host termite physiology investigated through transcriptomics. Four studies have revealed responses to immune challenges by both stereotypical and unprecedented immune-responsive genes ( Thompson et al, 2003 ; Yuki et al, 2008 ; Gao et al, 2012 ; Hussain et al, 2013 ). Finally, an emerging theme has been to investigate pathogen-xenobiotic interactions at the transcriptome level ( Husseneder and Simms, 2014 ; Sen et al, 2015 ).…”
Section: Omic Studies In Termites: What Has Been Revealed? mentioning
confidence: 99%
“…However, some studies have shown that subterranean termites have evolved many physiological mechanisms to deal with the challenges pathogens present. Hussain et al [3] identified 439 immune-related sequences (i.e., pattern recognition receptors, signal modulators, signal transducers, and effectors) from Coptotermes formosanus Shiraki that were infected by entomopathogenic fungi and bacteria. Some termites and their symbiotic actinobacteria can produce various β-1,3-glucanases and antibiotics to prevent the germination of entomopathogenic fungi [4][5][6].…”
Section: Introductionmentioning
confidence: 99%